2012
DOI: 10.1158/0008-5472.can-11-3132
|View full text |Cite
|
Sign up to set email alerts
|

Pten Loss and RAS/MAPK Activation Cooperate to Promote EMT and Metastasis Initiated from Prostate Cancer Stem/Progenitor Cells

Abstract: PTEN loss or PI3K/AKT signaling pathway activation correlates with human prostate cancer progression and metastasis. However, in preclinical murine models, deletion of Pten alone fails to mimic the significant metastatic burden that frequently accompanies the end stage of human disease. To identify additional pathway alterations that cooperate with PTEN loss in prostate cancer progression, we surveyed human prostate cancer tissue microarrays and found that the RAS/MAPK pathway is significantly elevated both in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
397
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(423 citation statements)
references
References 41 publications
(67 reference statements)
25
397
1
Order By: Relevance
“…Next, we continued to determine whether miR-19 positively modulates EMT, migration, and invasiveness of cancer cells in vitro via regulation of PTEN. Increasing evidence supports that inactivation or downregulation of the tumor suppressor PTEN can trigger EMT of cancer cells, [60][61][62][63] which then promoted the invasion and metastasis of various cancers including lung cancer. 42,[49][50][51][52][53][54][55][56][57] It has been reported that PTEN negatively regulated the PI3K/ Akt pathway through the dephosphorylation of PI(3,4,5)P3, and ultimately participated in the regulation of cell cycle, proliferation, apoptosis, adhesion, and EMT during cancer progress.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we continued to determine whether miR-19 positively modulates EMT, migration, and invasiveness of cancer cells in vitro via regulation of PTEN. Increasing evidence supports that inactivation or downregulation of the tumor suppressor PTEN can trigger EMT of cancer cells, [60][61][62][63] which then promoted the invasion and metastasis of various cancers including lung cancer. 42,[49][50][51][52][53][54][55][56][57] It has been reported that PTEN negatively regulated the PI3K/ Akt pathway through the dephosphorylation of PI(3,4,5)P3, and ultimately participated in the regulation of cell cycle, proliferation, apoptosis, adhesion, and EMT during cancer progress.…”
Section: Discussionmentioning
confidence: 99%
“…The RAS/MAPK pathway is significantly elevated in both primary and metastatic prostate cancer, and its activation promotes aggressive tumor behavior, but there is no information about its implication in tumor initiation. 36,37 Although CHKB has been shown to be involved in carcinogenesis in different types of solid tumors, to our knowledge, it has not been studied in human prostate cancer. 38 Different metalloproteinases, including MMP13, which has previously been linked to prostate cancer, were also up-regulated in the ODC-overexpressing cells in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The profound changes in cytoskeletal architecture that occur during EMT, together with a reduction in intercellular adhesion and an increase in motility, are fundamental to the metastatic process, enabling these cells to break through the basal membrane and migrate over long distances (21). The EMT is considered to be a significant step in the invasive cascade, facilitating the migration of tumor cells from their site of origin and their dissemination to distant tissues (22). EMT is a complex, stepwise phenomenon that is involved in embryonic development, as well as other physiological and pathological conditions, playing a role in enhancing the invasive and metastatic behavior of cancer cells.…”
Section: Discussionmentioning
confidence: 99%